Evidence for Plastic Processes in Migraine with Aura: A Diffusion Weighted MRI Study - Szabó, Nikoletta; Faragó, Péter; Király, András; Veréb, Dániel; Csete, Gergő; Tóth, Eszter; Kocsis, Krisztián; Kincses, Bálint; Tuka, Bernadett; Párdutz, Árpád; Szok, Délia; Tajti, János; et al. (Frontiers in Neuroanatomy, 2018)
Background: Formerly white matter abnormalities in a mixed group of migraine patients with and without aura were shown. Here we aimed to explore white matter alterations in a homogeneous group of migraineurs with aura and to delineate possible relationships between white matter changes and clinical variables. Methods: Eighteen patients with aura, twenty-five migraine patients without aura and twenty-eight controls were scanned on a 1.5T MRI scanner. Diffusivity parameters of the white matter were estimated and compared between patients’ groups and controls using whole-brain tract-based spatial statistics. Results: Decreased radial diffusivity (p<0.036) was found bilaterally in the parieto-occipital white matter, the corpus callosum, and the cingular white matter of migraine with aura patients compared to controls. Migraine without aura patients showed no alteration compared to controls. Migraine with aura compared to migraine without aura showed increased fractional anisotropy (p<0.048) in the left parieto-occipital white matter. In migraine with aura a negative correlation was found between axial diffusivity and disease duration in the left superior longitudinal fascicle (left parieto-occipital region) and in the left corticospinal tract (p<0.036) and with the number of the attacks in the right superior longitudinal fascicle (p<0.048). Conclusions: We showed for the first time that there are white matter microstructural differences between these two subgroups of migraine and hence it is important to handle the two groups separately in further researches. We propose that degenerative and maladaptive plastic changes coexist in the disease and the diffusion profile is a result of these processes.